The founding of Kwong Wai Shiu free hospital: reconciling modernity and tradition in healthcare in Singapore between the 1890s to 1911 - Tan, Jamie Yan Lin (Nanyang Technological University, 2024)
This thesis is an examination of the reconciliation of “modernity” and “tradition” in healthcare in Singapore between the 1890s and 1911, amid the advent of infectious diseases. The impact of infectious diseases redefined medical practices not only in colonial Singapore, but also across the expansive Chinese medical network. These diseases prompted a re-evaluation of medicine and medical practices, reshaping the landscape of healthcare in multiple regions. In colonial Singapore, there was a notable shift towards reconciling "modern" Western medical systems with "traditional" Chinese medical practices in response to evolving healthcare needs. This reconciliation of Chinese and Western medical systems was exhibited in many spaces, one of which was in the Kwong Wai Shiu Free Hospital (KWSFH). Established in 1911, the KWSFH stands out as the first modern Chinese hospital in Singapore to offer both Western and Chinese medicine. The establishment of the hospital challenges prevailing narratives of contention between medical systems, revealing a collaborative spirit amid local healthcare and broader Cantonese medical developments. Hence, this thesis seeks to locate the place of KWSFH within the shifting healthcare landscape of colonial Singapore and the broader Cantonese diaspora by examining the circumstances leading to its establishment.